Transcriptomic Analysis of High Fat Diet Fed Mouse Brain Cortex - Yoon, Gwangho; Cho, Kyung A; Song, Juhyun; Kim, Young-Kook (Frontiers in Genetics, 2019)
High fat diet can lead to metabolic diseases such as obesity and diabetes known to be chronic inflammatory diseases with high prevalence worldwide. Recent studies have reported cognitive dysfunction in obese patients is caused by a high fat diet. Accordingly, such dysfunction is called “type 3 diabetes” or “diabetic dementia”. Although dysregulation of protein-coding genes has been extensively studied, profiling of noncoding RNAs including long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) has not been reported yet. Therefore, the objective of this study was to obtain profiles of diverse RNAs and determine their patterns of alteration in high fat fed brain cortex compared to normal brain cortex. To investigate regulatory roles of both coding and noncoding RNAs in high fat diet brain, we performed RNA sequencing of ribosomal RNA-depleted RNAs and identified genome-wide lncRNAs and circRNAs expression and co-expression patterns of mRNAs in high fat diet mouse brain cortex. Our results showed expression levels of mRNAs related to neurogenesis, synapse, and calcium signaling were highly changed in high fat diet fed cortex. In addition, numerous differentially expressed lncRNAs and circRNAs were identified. Our study provides valuable expression profiles and potential function of both coding and noncoding RNAs in high fat diet fed brain cortex.